USM, FIRST LOCAL PUBLIC UNIVERSITY PARTNERING WITH UNIVERSITE DE LORRAINE (UL), FRANCE FOR COTUTELLE Ph.D. PROGRAMME - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 9 October 2016 – Universiti Sains Malaysia (USM) has pioneered the CoTutelle PhD Programme between public universities (UA) in Malaysia and Universite De Lorraine (UL) France since 1999, with the official signing of the Memorandum of Understanding (MoU) in 2002 involving the USM School of Chemical Sciences.